IMPLEMENTASI KEBIJAKAN PEMBEBASAN TANAH UNTUK PELEBARAN JALAN DI KOTA PONTIANAK (STUDI KASUS PEMBEBASAN TANAH DI JALAN PROF. M. YAMIN) - Munawir Munawir (Cross-border, 2018)
The purpose of this study is to determine what obstacles or obstacles in the process of road widening at Jln Prof. M. Yamin and the efforts made to overcome it. In this study, researchers used a descriptive type, namely explaining phenomena in depth through data collection. Descriptive research is the steps to re-interpret objects about the state of social phenomena contained in the problem under study. The descriptive method the researcher uses to describe or describe how the form of "Implementation of Land Acquisition Policy for Road Widening in Pontianak City", the results of the researchers show that in land acquisition, permits and community pressure to carry out the road widening are procedural steps for public works. provide cooperation in land acquisition measures for road widening in the city of Pontianak. In accordance with the results of the research obtained, it is suggested for the City Government, especially PU, to be careful with the existing procedures, if the socialization is not evenly distributed it will raise public disappointment to the City Government, especially PU, which is responsible for implementing the road widening project, and PU is required to commit. with tenders that do not change.